PSIDIUM GUAJAVA L. LEAF EXTRACT: ANTIBACTERIAL POTENTIAL AND PHYTOCHEMICAL ANALYSIS AGAINST ESCHERICHIA COLI FROM STOOL SAMPLES OF CHILDREN ATTENDING GUSAU SPECIALIST HOSPITAL - Bello , Amina Fatima (Research Journal of Health, Medicine and Nursing, 2024)
Guava (Psidium guajava) leaf is commonly used as a medicine against gastroenteritis and child diarrhea by those who cannot afford or do not have access to antibiotics. This study was aimed to determine the antibacterial activity of Guava leaf (Psidium guajava) extracts on E. coli using agar well diffusion method. Two different extracts were obtained from the guava leaf (aqueous soluble and ethyl acetate soluble extracts). Psidium guajava leaves were extracted with water and ethyl acetate using maceration extraction method. Phytochemical screening of the Psidium guajava leaf extracts was carried out using standard methods. Agar well diffusion and agar dilution methods were employed to determine the zone of inhibition, minimum inhibitory concentration, and minimum bactericidal concentration. The antibacterial test results showed that the Psidium guajava ethyl acetate and aqueous extracts have potential antimicrobial activity against Gramnegative bacteria. The Ethyl acetate extract showed the maximum zone of inhibition on test isolates (17mm at 100mg/ml) While the Aqueous extract showed the least inhibitory effect on test isolates (8mm at a concentration of 12.5mg/ml). The minimum inhibitory concentration (MIC) showed that both E. coli isolates was sensitive to both Ethyl acetate and aqueous extract (at the lowest concentration of 12.5mg/ml). The minimum bactericidal concentration (MBC) of aqueous extract was 100mg/ml for both the isolates and ethyl acetate extract for 50mg/ml for both the isolates, this result indicate that Guava leaf extracts have antibacterial activities against the test isolates, and the Ethyl acetate extract is more effective compared to the aqueous extract.